Pembelajaran Sosiologi Pendidikan Pada Calon Guru Ilmu Pengetahuan Sosial di UINSU - Eka Susanti; Anna Wahyuni; Rina Aulia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research aims to conduct an evaluative analysis of educational sociology learning among prospective social science teachers at the North Sumatra State Islamic University (UINSU) using a quantitative approach. A total of 70 students formed the population, and a sample of 30 students was selected using purposive sampling techniques. The data collection instrument is in the form of a questionnaire with structured questions covering aspects of evaluating course material, teaching methods, student empowerment, relevance of material to preparation to become a social studies teacher, satisfaction with teachers and tutors, availability of resources, collaboration between students, teaching preparation, and readiness to face challenges. in the future. The results of data analysis show that the overall evaluation of educational sociology lecture material received a "Very Good" rating with an average score of 94.85%. Various indicators such as the level of understanding, student involvement, and skill development related to sociological concepts received positive assessments. All other aspects, including student empowerment, relevance of material, satisfaction with instructors, availability of resources, collaboration between students, teaching preparation, and readiness to face future challenges, were also rated "Very Good." The sociology of education learning at UINSU is considered very good by students, and the evaluation results can be the basis for developing learning programs in the future. These findings provide a positive picture of the quality of educational sociology learning and indicate the success of the program in providing conceptual understanding, practical skills, and career preparation for prospective social science teachers.